Schopf-Schulz-Passarge syndrome - Kinjal D Rambhia; Vidya Kharkar; Sunanda Mahajan; Uday S Khopkar (Wolters Kluwer Medknow Publications, 2018)
Schopf-Schulz-Passarge syndrome (SSPS) is a rare type of ectodermal dysplasia that has autosomal recessive inheritance. It is characterized by palmoplantar keratoderma, hypodontia, hypotrichosis, nail dystrophy, and multiple periocular and eyelid apocrine hidrocystomas. A 36-year-old male presented with multiple eyelid and periocular apocrine hidrocystomas, ichthyosis, palmoplantar keratoderma, hypodontia, nail dystrophy, and thin scalp hair. Skin biopsy from a periocular lesion revealed cyst lined with smooth, thin epithelium, and few areas revealed foci of decapitation secretion consistent with apocrine hidrocystoma. The patient was diagnosed with SSPS.